Cerebral Lipids in Rett Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The lipid membrane composition of cerebral tissue from five patients, age 12-30 years, and from 14 age-matched controls was studied at the Department of Psychiatry and Neurochemistry and Pediatrics, University of Goteborg, Goteborg, Sweden.